Review paperThe role of endothelin in stroke: Experimental data and underlying pathophysiology - Schaller, Bernhard J. (Archives of Medical Science, 2006)
The role of endothelin in functional and structural changes after stroke is only partly understood: synthesis and release of the potent vasoconstrictor peptide endothelin-1 increases following ischemia and mediates the delayed hypoperfusion associated with ischemia, but the role of the other two endothelin subtypes remains unclear. Only little is known about its mode of action in ischemia. Recently developed selective peptide and non-peptide antagonists and agonists acting at the level of endothelin receptors provide useful tools for further investigation of the physiological role of endothelin and its impact on pathophysiological processes in different neurological diseases including ischemic, nonhemorrhagic stroke and cerebral vasospasm. The present review supports experimental and clinical evidence that vasoactive mediators, and endothelin-1 in particular, are important contributors to the pathogenesis of cerebral ischemic damage in animal models and in humans. Special reference is given to explain the few clinical data in the light of experimental results.